Natural and azido fatty acids inhibit phosphate transport and activate fatty acid anion uniport mediated by the mitochondrial phosphate carrier - Engstová, H; Zácková, M; Růzicka, M; Meinhardt, A; Hanus, J; Krämer, R; Jezek, P (The Journal of biological chemistry, 2001)
The electroneutral P(i) uptake via the phosphate carrier (PIC) in rat liver and heart mitochondria is inhibited by fatty acids (FAs), by 12-(4-azido-2-nitrophenylamino)dodecanoic acid (AzDA) and heptylbenzoic acid ( approximately 1 microm doses) and by lauric, palmitic, or 12-azidododecanoic acids ( approximately 0.1 mm doses). In turn, reconstituted E. coli-expressed yeast PIC mediated anionic FA uniport with a similar pattern leading to FA cycling and H(+) uniport. The kinetics of P(i)/P(i) exchange on recombinant PIC in the presence of AzDA better corresponded to a competitive inhibition mechanism. Methanephosphonate was identified as a new PIC substrate. Decanephosphonate, butanephosphonate, 4-nitrophenylphosphate, and other P(i) analogs were not translocated and did not inhibit P(i) transport. However, methylenediphosphonate and iminodi(methylenephosphonate) inhibited both electroneutral P(i) uptake and FA cycling via PIC. AzDA analog 16-(4-azido-2-nitrophenylamino)-[(3)H(4)]-hexadecanoic acid ((3)H-AzHA) bound upon photoactivation to several mitochondrial proteins, including the 30- and 34-kDa bands. The latter was ascribed to PIC due to its specific elution pattern on Blue Sepharose and Affi-Gel. (3)H-AzHA photolabeling of recombinant PIC was prevented by methanephosphonate and diphosphonates and after premodification with 4-azido-2-nitrophenylphosphate. Hence, the demonstrated PIC interaction with monovalent long-chain FA anions, but with divalent phosphonates of short chain only, indicates a pattern distinct from that valid for the mitochondrial uncoupling protein-1.
Keywords: kinetika; Dose-Response Relationship, Drug; Rats; vztah mezi dávkou a účinkem léčiva; iontový transport; mitochondrie; Biological Transport, Active; Carrier Proteins; Fatty Acids; Rats, Wistar; Phosphate-Binding Proteins; krysa rodu Rattus; Ion Transport; Palmitic Acids; Lauric Acids; zvířata; proteiny vázající fosfáty; Affinity Labels; Diphosphonates; Kinetics; Phosphates; Mitochondria; mastné kyseliny; kyseliny palmitové; kyseliny laurové; afinitní značky; potkani Wistar; fosfáty; aktivní transport; bisfosfonáty; transportní proteiny; Animals